Flavonoids in natural products for the therapy of liver diseases: progress and future opportunities - Liao, Yanmei; Lv, Fei; Quan, Tianwen; Wang, Chuan; Li, Jike (Frontiers in Pharmacology, 2024)
The liver is the largest, important organ and the site for essential biochemical reactions in the human body. It has the function to detoxify toxic substances and synthesize useful biomolecules. Liver diseases related complications represent a significant source of morbidity and mortality worldwide, creating a substantial economic burden. Oxidative stress, excessive inflammation, and dysregulated energy metabolism significantly contributed to liver diseases. Therefore, discovery of novel therapeutic drugs for the treatment of liver diseases are urgently required. For centuries, flavonoids and their preparations which have the beneficial health effects in chronic diseases have been used to treat various human illnesses. Flavonoids mainly include flavones, isoflavones, flavanols, dihydroflavones, dihydroflavonols, anthocyanins and chalcones. The primary objective of this review is to assess the efficacy and safety of flavonoids, mainly from a clinical point of view and considering clinically relevant end-points. We summarized the recent progress in the research of hepatoprotective and molecular mechanisms of different flavonoids bioactive ingredients and also outlined the networks of underlying molecular signaling pathways. Further pharmacology and toxicology research will contribute to the development of natural products in flavonoids and their derivatives as medicines with alluring prospect in the clinical application.